PENGELOLAAN MEDIA SOSIAL SEBAGAI SARANA EDUKASI DAN DAKWAH BAGI SISWA DI SMA MUHAMMADIYAH 2 TANJUNG ENIM - Iqbal, Ahmad; Mulya, Bayu Cahyadi; Suryani, Melly; Hariani, Lia; Ramdhan, Akmal; Rusmin, Rusmin; Shofiah, Robiatun; Putra, Deni; Hidayatullah, M Rizki; Dahirin, Dahirin (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract: This study aims to analyze the management of social media, specifically Instagram and TikTok, as an educational preaching (dakwah) tool for students at SMA Muhammadiyah 2 Tanjung Enim. The research method used is a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with Islamic Education (PAI) teachers and students, as well as documentation of digital preaching activities in the school environment. Data analysis techniques included data collection, data presentation, verification, and drawing conclusions. Based on the results and discussion, Instagram and TikTok were found to be effective for delivering Islamic messages in a creative, engaging way that aligns with the characteristics of the digital generation. Students are not only recipients of information but also producers of preaching content, demonstrating active involvement in the internalization of Islamic values. The success of preaching through social media is determined by content quality, teacher guidance, and understanding of media ethics. This study recommends strengthening digital preaching strategies in schools through collaboration and media skills training.Keywords: Education and Preaching, Social Media, Students, ManagementAbstrak: Penelitian ini bertujuan untuk menganalisis tentang pengelolaan media sosial, khususnya Instagram dan TikTok, sebagai sarana dakwah edukatif bagi siswa SMA Muhammadiyah 2 Tanjung Enim. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan studi kasus. Data dikumpulkan melalui observasi, wawancara mendalam dengan guru PAI dan siswa, serta dokumentasi aktivitas dakwah digital di lingkungan sekolah. Teknik analisisÂ  data melalui pengumpulan data, penyajian data, verifikasi dan penarikan keksimpulan. Berdasarkan hasil dan pembahasan bahwa Instagram dan TikTok efektif digunakan dalam menyampaikan pesan-pesan keislaman secara kreatif, menarik, dan sesuai dengan karakteristik generasi digital. Siswa tidak hanya menjadi penerima informasi, tetapi juga produsen konten dakwah, yang menunjukkan keterlibatan aktif dalam proses internalisasi nilai-nilai Islam. Keberhasilan dakwah melalui media sosial ditentukan oleh kualitas konten, pendampingan guru, dan pemahaman etika bermedia. Penelitian ini merekomendasikan perlunya penguatan strategi dakwah digital di sekolah berbasis kolaborasi dan pelatihan keterampilan media.Kata Kunci: Edukasi dan Dakwah, Media Sosial, Siswa, Pengelolaan